Stars and Ribbons : Winter Wassailing in Wales. - Ifans, Rhiannon (Cardiff : University of Wales Press, 2022)
This book provides Welsh wassailing songs in their original language, translated into English and with musical notation, together with a vivid introduction to their significance within the society in which they were sung.
Appendix: Verse Forms -- Bibliography
Description based upon print version of record.
eBooks on EBSCOhost
Keywords: Folk songs, Welsh -- History and criticism; Folk music -- Wales -- History and criticism; Chansons folkloriques galloises -- Histoire et critique; Folk music; Folk songs, Welsh; Wales; Criticism, interpretation, etc